2021
DOI: 10.1002/ijc.33461
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nonleukemic cellular subcompartments reconstructs clonal evolution of acute myeloid leukemia and identifies therapy‐resistant preleukemic clones

Abstract: To acquire a better understanding of clonal evolution of acute myeloid leukemia (AML) and to identify the clone(s) responsible for disease recurrence, we have comparatively studied leukemia‐specific mutations by whole‐exome‐sequencing (WES) of both the leukemia and the nonleukemia compartments derived from the bone marrow of AML patients. The T‐lymphocytes, B‐lymphocytes and the functionally normal hematopoietic stem cells (HSC), that is, CD34+/CD38−/ALDH+ cells for AML with rare‐ALDH+ blasts (<1.9% ALDH+ cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Although our report is limited to a single case, these data support the concept that mutations in genes implied in epigenetic regulation are initial events in clonal evolution and they arose from preleukemic progenitor cells, being early founder hits prior to leukemogenic events [3,4]. Furthermore, our data showed that NPM1 mutation represent a secondary hit in agreement with previous published reports that considered it a leukemogenic event, driving progression to AML [3,4,28]. The presence of both DNMT3A and NPM1 mutations in the granulocytic population indicates their appearance in early stages of hematopoiesis, giving rise to hematopoietic clones that persist over time and survive to different therapies [3,4].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although our report is limited to a single case, these data support the concept that mutations in genes implied in epigenetic regulation are initial events in clonal evolution and they arose from preleukemic progenitor cells, being early founder hits prior to leukemogenic events [3,4]. Furthermore, our data showed that NPM1 mutation represent a secondary hit in agreement with previous published reports that considered it a leukemogenic event, driving progression to AML [3,4,28]. The presence of both DNMT3A and NPM1 mutations in the granulocytic population indicates their appearance in early stages of hematopoiesis, giving rise to hematopoietic clones that persist over time and survive to different therapies [3,4].…”
Section: Discussionsupporting
confidence: 92%
“…The present report shows the FLT3-ITD as the late event after DNMT3A and NPM1 mutations, according to other papers that described proliferative mutations in genes involved in signaling as final events in leukemogenesis [28,30]. Therefore, the most likely scenario, confirmed by the fishplot prediction, is that mutations were acquired sequentially in an ancestral clone giving rise to new clonal populations of cells that would coexist with the surviving parental clones.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Acute myeloid leukemia arises either de novo, in which the earliest mutation triggers the development of the disease, or may expand from other hematological malignancies following the stepwise increase of chromosomal and/or genetic/epigenetic abnormalities [55][56][57][58][59]. Until now, the mechanisms supporting the regulation and clinical significance of the Ca 2+ /mitochondria pathways have remained mostly unidentified in LSCs.…”
Section: Lscs and Amlmentioning
confidence: 99%
“…These mutations alone are incapable of inducing leukemia and appear as precursor events to late mutations that transform pre-LSCs into LSCs, which is shown in Figure 1. Therefore, the genetic alterations present in LSCs are related to proliferation and active signaling (26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Pre-leukemic Stem Cell and Leukemic Stem Cellmentioning
confidence: 99%